(untitled) (mathematica didactica, 2003)
This paper discusses different mental models of the concept of vector space thatwere revealed by three students in a qualitative empirical study. Three categories of conceptionsare presented with respect to their adequacy, their limitations, and the chances of further development and amelioration.